Microglial phagocytosis of living photoreceptors contributes to inherited retinal degeneration. Issue 9 (2nd July 2015) - Zhao, Lian; Zabel, Matthew K; Wang, Xu; Ma, Wenxin; Shah, Parth; Fariss, Robert N; Qian, Haohua; Parkhurst, Christopher N; Gan, Wen‐Biao; Wong, Wai T
Abstract: Retinitis pigmentosa, caused predominantly by mutations in photoreceptor genes, currently lacks comprehensive treatment. We discover that retinal microglia contribute non‐cell autonomously to rod photoreceptor degeneration by primary phagocytosis of living rods. Using rd10 mice, we found that the initiation of rod degeneration is accompanied by early infiltration of microglia, upregulation of phagocytic molecules in microglia, and presentation of "eat‐me" signals on mutated rods. On live‐cell imaging, infiltrating microglia interact dynamically with photoreceptors via motile processes and engage in rapid phagocytic engulfment of non‐apoptotic rods. Microglial contribution to rod demise is evidenced by morphological and functional amelioration of photoreceptor degeneration following genetic ablation of retinal microglia. Molecular inhibition of microglial phagocytosis using the vitronectin receptor antagonist cRGD also improved morphological and functional parameters of degeneration. Our findings highlight primary microglial phagocytosis as a contributing mechanism underlying cell death in retinitis pigmentosa and implicate microglia as a potential cellular target for therapy. Synopsis: In Retinitis pigmentosa (RP), retinal microglia are shown to potentiate the rate of rod photoreceptor death via phagocytic and pro‐inflammatory mechanisms. This process may be common to multiple genetic etiologies of RP in mouse models and in human patients. Microglial phagocytosis of rod photoreceptors was initiated at the start of rod apoptosis with early infiltration of retinal microglia into the outer retina, upregulation of phagocytic molecules in microglia, and exposure of PS, an "eat‐me" signal, on rod photoreceptors. Microglial phagocytosis of rods included apoptotic cells but also cells that have not yet been committed to apoptosis and are negative for apoptotic markers, indicating microglial clearance of stressed but living rods. Infiltrating microglia demonstrated dynamic interactions with photoreceptors via motile processes that culminate in the overt phagocytosis of non‐apoptotic rods. The contribution of infiltrating microglia to rod demise was demonstrated by structural and functional rescue of photoreceptor degeneration. Microglia‐directed interventions may be of potential utility in prolonging the survival of photoreceptors and deferring irreversible vision loss associated with RP of different genetic etiologies. Abstract : In Retinitis pigmentosa (RP), retinal microglia are shown to potentiate the rate of rod photoreceptor death via phagocytic and pro‐inflammatory mechanisms. This process may be common to multiple genetic etiologies of RP in mouse models and in human patients.